A compreensão rebelde de Nise da Silveira: uma mulher à frente do seu tempo - Vidal de Castro Ortiz, Ana Cristina; Falco Ortiz, Pedro Henrique (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The brazilian psychiatrist Nise da Silveira called herself “a rebel psychiatrist” for treading through different and challenging paths both in her private and professional lives. Considered to be a pioneer of humanizing therapies for patients diagnosed with mental and psychosocial disorders, such as schizophrenia, Nise was a brave woman who defied her peers as well as the medical consensus of her time through her rejection of the violent and dehumanizing methods adopted by psychiatric hospitals in Brazil. She has created the Images of the Unconscious Museum and pioneered in art therapy and animal-assisted therapy at Psychiatric Center Pedro II, in Rio de Janeiro.